Exploring voyeurism: a review of research - Wdowiak, Krystian; Maciocha, Agnieszka; Wąż, Julia; Witas, Aleksandra; Drogoń, Justyna; Gwóźdź, Edyta; Muzyka, Adrian; Rydzek, Julia; Gardocka, Ewa (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Voyeurism is characterized by recurrent and intense sexual arousal derived from observing unsuspecting individuals who are naked, disrobing, or engaging in sexual activity. Suggested risk factors for developing voyeurism include childhood sexual abuse, substance misuse, hypersexuality, emotional dysregulation, poor mental health, maladaptive coping strategies, and external pressures The aim of this publication is to discuss various aspects of voyeurism based on the latest literature. Review Methods: The PubMed database was searched to find scientific articles in which the terms “voyeurism” or “voyeuristic” appear in the title, abstract, or keywords. Brief Description of the State of Knowledge: Estimating the global prevalence of voyeurism is challenging due to inconsistent data, with reported rates ranging from over 10% to approximately 30–40%. Studies consistently indicate that voyeuristic behavior is more common among men. It often exhibits a compulsive and repetitive nature and can serve as a precursor to other sexual crimes, such as sexual sadism or pedophilia. Treatment primarily involves cognitive behavioral therapy (CBT), with pharmacological support using SSRIs like fluoxetine and paroxetine, showing effectiveness. Summary: The authors highlight the importance of further exploration into this topic and emphasize the need for a more accurate understanding of voyeurism’s prevalence in the general population, as current data may be inconclusive.